2013
DOI: 10.1007/s12032-013-0486-y
|View full text |Cite
|
Sign up to set email alerts
|

FOLFIRI + bevacizumab as second-line therapy for metastatic colorectal cancer pretreated with oxaliplatin: a pooled analysis of published trials

Abstract: Irinotecan and infusional 5-fluorouracil-based chemotherapy (FOLFIRI) plus bevacizumab (FOLFIRI-B) is one of the most effective treatments of advanced colorectal cancer (CRC). However, this schedule is regarded more extensively as first-line therapy and its efficacy has not been proven in phase III randomised trials in oxaliplatin-pretreated patients. We have performed a systematic review through PubMed and EMBASE, including all prospective and retrospective publications exploring the efficacy of FOLFIRI-B as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…A recent large pooled analysis including 29 studies confirmed the indication in this setting [12]. This same association was found active also in pre-treated patients, as shown in another report pooling data from 11 studies [13]. Likewise, an oxaliplatin-based regimen was initially found to be more active when combined to bevacizumab [7]; subsequent pooled analysis confirmed this finding, too [14].…”
Section: Tumour Neo-angiogenesis and Bevacizumabmentioning
confidence: 66%
“…A recent large pooled analysis including 29 studies confirmed the indication in this setting [12]. This same association was found active also in pre-treated patients, as shown in another report pooling data from 11 studies [13]. Likewise, an oxaliplatin-based regimen was initially found to be more active when combined to bevacizumab [7]; subsequent pooled analysis confirmed this finding, too [14].…”
Section: Tumour Neo-angiogenesis and Bevacizumabmentioning
confidence: 66%
“…According to a systematic review (Phase II) bevacizumab in combination with FOLFIRI prolongs the median PFS to 8.3 months compared with FOLFIRI alone, in the second-line setting (15). XELIRI in combination with bevacizumab was associated with a median PFS of 8.3 months in the second-line setting in the BIX study (6), which is considerably longer than in the present study, where the median PFS was 4.6 months (where 49% of patients were treated with bevacizumab).…”
Section: Discussionmentioning
confidence: 99%
“…In this patient, bevacizumab was not started with the first-line FOLFOX regimen because the results of the NO16966 randomized phase III trial clearly showed that the addition of bevacizumab to FOLFOX was not associated with improved progression-free survival (HR 0.89, 97.5% CI 0.73-1.08), overall survival (OS) (HR 0.94, 95% CI 0.75-1.16), or overall response rate (38% in both arms) (6). The combination of FOLFIRI with bevacizumab (FOLFIRI-B) as second-line therapy for patients with metastatic CRC pretreated with oxaliplatin but not with bevacizumab was recently reviewed in a pooled analysis of retrospective and prospective trials involving 435 patients (7). The main conclusion was that FOLFIRI-B is a reasonable option for these patients.…”
Section: Thromboembolic Disease In Advanced Colorectal Cancer Treatedmentioning
confidence: 99%